Integrasi Perangkat Lunak Arcgis 9.3, Xampp, Mapserver for Window dan Geoserver dalam Rangka Penyusunan Peta Geologi Pulau Bangka Digital Berbasis Web - Franto Franto; Alim Bahri (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2015)
Geographic Information System is an information system that is used to enter, store, recall,process,analyze and output geographically referenced data or geospatial. By using GIS will be easierfor decision makers to analyze the data. In this paper, the author makes the design of GIS localhostfor the manufacture of Geographical Information Systems Geology Bangka Island using ArcGIS 9.3,Xampp, Mapserver and GeoServer.Utilization of several applications open source simple andapplicable in the form of web server used is Xampp, the database server is used MySQL andmanagement applications MySQL used PhpMyAdmin resulting Web SIG on geological aps digitalBangka Island and their attributes that can be used as information about the initial data for analysisadvanced.